2012
DOI: 10.1261/rna.031567.111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring purine N7 interactions via atomic mutagenesis: The group I ribozyme as a case study

Abstract: Atomic mutagenesis has emerged as a powerful tool to unravel specific interactions in complex RNA molecules. An early extensive study of analogs of the exogenous guanosine nucleophile in group I intron self-splicing by Bass and Cech demonstrated structure-function relationships analogous to those seen for protein ligands and provided strong evidence for a wellformed substrate binding site made of RNA. Subsequent functional and structural studies have confirmed these interacting sites and extended our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…The double-deaza mutant (U6-7cA59/7cG60) led to the accumulation of splicing intermediates (Figure 3). Model studies have shown that deaza substitutions in a helix negatively affect helix stability by reducing stacking, hydration and/or cation interaction (58,59). The double-deaza mutant would therefore be predicted to lead to weakened base stacking, suggesting that the A59/G60 stack in the U2/U6 RNA core (Figure 5) might have a stabilising effect on the structural transitions between steps 1 and 2 of splicing.…”
Section: Discussionmentioning
confidence: 99%
“…The double-deaza mutant (U6-7cA59/7cG60) led to the accumulation of splicing intermediates (Figure 3). Model studies have shown that deaza substitutions in a helix negatively affect helix stability by reducing stacking, hydration and/or cation interaction (58,59). The double-deaza mutant would therefore be predicted to lead to weakened base stacking, suggesting that the A59/G60 stack in the U2/U6 RNA core (Figure 5) might have a stabilising effect on the structural transitions between steps 1 and 2 of splicing.…”
Section: Discussionmentioning
confidence: 99%
“…This can be determining for RNA base pairing ( 8 , 9 ), for RNA recognition of other nucleic acids (e.g. DNA, 2â€Č-OCH 3 RNA) ( 6 ), proteins ( 3 ), small molecules ( 8 ), and ions ( 9 ), and this can also be crucial with respect to RNA-catalyzed reactions ( 4 , 10–13 ). Concerning the latter, atomic mutagenesis lead to our current in-depth understanding of the chemical mechanism of phosphodiester cleavage of the recently discovered twister and pistol ribozymes ( 14–16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable deazanucleosides for informative RNA atomic mutagenesis experiments are 7-deazaadenosine (c 7 A) ( 4 , 11–13 , 15 , 16 ), 3-deazaadenosine (c 3 A) ( 14 , 20 ), 1-deazaadenosine (c 1 A) ( 11 , 12 , 14 , 20 ), 7-deazaguanosine (c 7 G) ( 13 , 15 ) and 3-deazacytidine (c 3 C) ( 13 , 21 ). Moreover, 3-deazaguanosine (c 3 G) and 1-deazaguanosine (c 1 G) would be highly useful for RNA atomic mutagenesis, however, such studies are very rare ( 22 ) because synthetic access to appropriate phosphoramidite building blocks and to the corresponding RNAs is challenging ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…[19] Finally, in the context of RNA, DAG has been used as an analog to map out the interactions of the exogenous guanosine molecule in the Tetrahymena group I ribozyme, and shown to compromise neither its binding nor its reactivity. [20] Figure 1. Structure of (a) guanine (G); (b) 7-substituted-7-deaza-8-azaguanine (7-X-DAG); (c) isoguanine (iG); (d) 7-substituted-7-deaza-8-aza-isoguanine (7-X-DAiG) with conventional numbering of purines.…”
Section: Introductionmentioning
confidence: 99%